The Utilization of Mentoring and Media Counseling in Learning Information Services at Santo Paulus High School in Pontianak - Sunardi Sunardi; Indri Astuti; Aloysius Mering (International Journal of Learning and Instruction (IJLI), 2019)
This research is conducted based on the importance of the use of guidance and counselling media in providing learning information service to students. The purpose of the research is to provide descriptions on the use of guidance and counselling media in providing learning information service to students at SMA Santo Paulus Pontianak. The description focuses on the types of the media, the methods of service, the intensity of the use of the media and the impacts on students. It is qualitative research which applies interview method in its data gathering. This research provides the information that the types of media used in learning information service vary, such as powerpoint slides, guidance boards, problem boxes, films, leaflets and brochures, and electronic device that fits the types and the needs of the service. The learning information service methods applied at SMA Santo Paulus Pontianak are presentations, discussions, questions-answers, and sharing sessions. The students are allowed to choose the methods of guidance based on their characteristics. The intensity of the use of guidance and counselling media at SMA Santo Paulus Pontianak is managed based on the types of the media and the time and space limitation. The purpose of the media in the learning information service increases the students’ level of focus and interest in the service. The students’ increasing focus and interest towards the guidance and counselling service ultimately lead to the positive impacts on their characters, so that they become more responsible for their learning at school and home.Keywords: Media, Guidance and Counseling, Learning Information Service